KETIMPANGAN DISTRIBUSI SUMBER DAYA TENAGA PENDIDIK DAERAH PERBATASAN DI KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI TAHUN 2015-2016 - Kamisah "; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
research would like to see what are the Authority of Education Department and Regional Personnel Agency and Programs in Inequality Distribution of Resource of Border Area Educator in Kecamatan Rangsang Pesisir Regency of Kepulauan Meranti in 2015-2016. The main problem that became the phenomenon in this research is to see in Meranti Islands Regency one of them in Rangsang Pesisir Subdistrict in the unequal distribution of educator resource become problems that often happen like, supporting facilities and infrastructure for student learning that is not bekualitas, lack of accessibility in economy, and lack of society in adaptation.The purpose of this study is first to describe the authority of the Department of Education and Regional Personnel Agency in Resolving or Distributing Inequality of Border Area Educational Personnel in Kecamatan Rangsang Pesisir Kabupaten Meranti Islands, secondly to describe the educational equity program, Secondary Education Program, Education Quality Improvement Program and Teachers, Primary and Secondary Education Programs by the Department of Education and Regional Personnel Board in Kepulauan Meranti District in 2015-2016. The type of this research used is the type of descriptive research with qualitative analysis method. Technique of data collecting done by observation, interview and documentation. While data analysis is done with with qualitative analysis.The results of this study indicate that the Authority and the Program of Education and Regional Personnel Board in distributing the resources of educators of border areas in the District of Rangsang Pesisir of Kepulauan Meranti Regency in 2015-2016, has not been able to perform well, so in the equity Senior High School educators have been taken by the Province in 2017. It is hoped that in the future it is necessary to affirm the policy of local government and related institutions in advancing education in the future.Keywords: Inequality, Resource Distribution of Teachers